Population dynamics among six major groups of the Oryza rufipogon species complex, wild relative of cultivated Asian rice - Kim, Hyunjung; Jung, Janelle; Singh, Namrata; Greenberg, Anthony; Doyle, Jeff J.; Tyagi, Wricha; Chung, Jong-Wook; Kimball, Jennifer; Hamilton, Ruaraidh Sackville; McCouch, Susan R. (Springer, 2016)
Understanding population structure of the wild progenitor of Asian cultivated rice (O. sativa), the Oryza rufipogon species complex (ORSC), is of interest to plant breeders and contributes to our understanding of rice domestication. A collection of 286 diverse ORSC accessions was evaluated for nuclear variation using genotyping-by-sequencing (113,739 SNPs) and for chloroplast variation using Sanger sequencing (25 polymorphic sites). Six wild subpopulations were identified, with 25 % of accessions classified as admixed. Three of the wild groups were genetically and geographically closely related to the O. sativa subpopulations, indica, aus and japonica, and carried O. sativa introgressions; the other three wild groups were genetically divergent, had unique chloroplast haplotypes, and were located at the geographical extremes of the species range. The genetic subpopulations were significantly correlated (r2 = 0.562) with traditional species designations, O. rufipogon (perennial) and O. nivara (annual), differentiated based on morphology and life history. A wild diversity panel of 95 purified (inbred) accessions was developed for future genetic studies. Our results suggest that the cultivated aus subpopulation is most closely related to an annual wild relative, japonica to a perennial wild relative, and indica to an admixed population of diverse annual and perennial wild ancestors. Gene flow between ORSC and O. sativa is common in regions where rice is cultivated, threatening the identity and diversity of wild ORSC populations. The three geographically isolated ORSC populations harbor variation rarely seen in cultivated rice and provide a unique window into the genetic composition of ancient rice subpopulations